Collaboration of the Stakeholders in Developing Community-Based Tourism in Terong Creative Village, Belitung - Santosa, Santosa; Saryani, Saryani; Susilowati, Heni; Setiaji, Yudi; Anggraini, Anggraini (Technium Social Sciences Journal, 2023)
Tourism village empowerment needs to collaborate with other communities/institutions (stakeholders), in order to accelerate and expand the tourism village movement to achieve its goals. This study aims to: 1) find out the potential of the Terong Belitung Creative Tourism Village destination; 2) find out the forms of collaboration that have been carried out by stakeholders in developing the Terong Belitung Creative Tourism Village; and 3) find out the steps taken by the manager of the Terong Creative Tourism Village in managing the village which is done in accordance with the community interests. This study used a qualitative approach and data collection methods by doing interviews, observation, and documentation. Participants or informants as a source of research data were 6 (six) parties consisting of BNI Bank, BCA Bank, PLN, Tourism Office of Belitung Region, The Government of Terong District, and the Tourism Village Managers. The results of this study indicate that 1) Potential destinations include: River and Sea Tourism in Mangrove Forest in Terong Village, Aik Rusa’ Berehun Tourism, Tebalu Simpor Laki Hill Tourism, Agritourism (Agriculture and Plantation), Catfish Pond Groups, Weaving Handicraft Group, Gambus Art and Culture Group, and the Community of Tourism Halfway House Management. 2) The roles of stakeholders are as Police Creator, Coordinator, Facilitator, Implementer, and also BNI, BCA, and PLN as the Accelerators. 3) The real form or contribution of the stakeholders especially from the bank and PLN is to build the homestays and the entrance gates to tourism village areas including the lighting system around the tourist village of Air Rusa Berehum (ARB), and also to conduct various culinary trainings and improvement of human resources training (HR). In improving the development of tourism villages, the role of stakeholders should run well. 4) The steps in managing a tourism village are being carried out by the planning stage, the implementation stage, and the last is the impact of benefits aspect stage.